Dynamics of Power Relations and Concordance Leadership Style in Policy Making: A Case Study of the Malang City Regional Legislative Council 2020 - Said, Moch. Fauzie (Jurnal Politik Profetik, 2025)
The mass corruption scandal that engulfed 41 out of 45 legislators in Malang City DPRD in 2018 serves as a striking reminder of how fragile democratic institutions can be when power becomes overly concentrated and accountability mechanisms are weak. Against this backdrop, this study aims to analyze the distribution of power and the interplay between structural dominance, leadership style, and political behavior in the Malang City DPRD, particularly in relation to its policy-making processes. Using a qualitative case study approach, the research draws on document analysis, interviews, and observation to capture the dynamics of legislative-executive relations and intra-party interactions. Findings show that PDI-P’s positional dominance enabled it to secure agenda-setting power, yet this structural advantage was exercised not through confrontational oversight but rather through a consensus-oriented, harmonious relationship with the executive. While fostering stability, this alignment weakened the checks and balances function, leading to policy capture by elites and reinforcing cartelized politics. The novelty of this research lies in integrating the positional approach, political behavior theory, and system analysis to reveal how structural dominance combined with weak legislative capacity produces institutional vulnerability to corruption. The policy implication is clear, strengthening legislative capacity, internal party democracy, and opposition mechanisms is essential to prevent elite capture and ensure that local legislatures genuinely serve as instruments of democratic accountability.